A Evaluasi Quick Ratio, Sales Growth Dan Total Asset Turn Over Terhadap Financial Distress - Hadi, Yulianto; Jamaludin, Ali; Rizal, Deni Saeful; HS, Vita Evelini; Fitri, Fitri; Malik, Rizki Kurnia (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The purposeof this study was to examine the effect of quick ratio, sales growth and total asset turn over to financial distress. The population in this study are textile and garment sub- sector companies listed on the Indonesia stock exchange (IDX) in 2017-2021. This research method uses a quantitative descriptive statistical analysis method. Sampling in this study uses a purposive sampling method, which is a sampling technique based on certain criteria. So that the sample used was 15 textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data from financial reports. The data was analyzed using panel data regression techniques assisted by the eviews 12. The results showed that the quick ratio partially did not have a significant effect on financial distress, sales growth partially had a nonsignificant effect on financial distress and total asset turn over partially had a significant effect on financial distress. As well as quick ratio, sales growth and total asset turn over simultaneously have a significant effect on financial distress.